Pediatric extramammary myofibroblastoma in the head and neck region: a case report - K. C., Sunil; Kumar, B. Y. Praveen; M. K., Varna Ravindran; Mali, Kiran (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
A rare form of mesenchymal neoplasm that typically presents in older men and women is mammary myofibroblastoma. Even so rarely, these benign tumours may occur outside of the breasts in soft tissues; which then are called mammary-type myofibroblastoma. There can be marked variability in the histological composition of these benign spindle cell tumours. Along the milk line is the commonest presentation of these extramammary myofibroblastoma. Here we have an 8 years old female patient presented to the department of otorhinolaryngology with a painless, fusiform swelling over the right lateral aspect of tongue in the past 6 months. Intra oral examination revealed a non-tender, non-ulcerated fusiform shaped mass approximately 3×2 cm firm in consistency arising from the right lateral border of the tongue. FNAC was done which showed spindle cell tumour tongue. The lesion was diagnosed as mammary type myofibroblastoma on immunohistochemistry.